PERILAKU SEKS PRANIKAH DALAM BERPACARAN (Studi Kasus Perilaku Seks Pranikah di Lingkungan Remaja di Kota Salatiga) - Susi Septi Harningrum; Daru Purnomo (Cakrawala Jurnal Penelitian Sosial, 2014)
Salatiga demographic situation shows that in a decade (2000-2010) the population growth rate has increased. Salatiga Religious Court said that there isa policy that caused the Marriage Dispensationof Marriage Relations, which one of the couple's age into the teen category. Hencethe need for a sociological study to examine the sexual behavior among adolescents. The purpose of this research is to describe the behavior of premarital sex among teenagers in dating, contributing factorsan dthe impact on social life. This research is adescriptive study with a qualitative approach. The unit of observation is dating the teen had premarital sex, while the unit of analysis is the premarital sexual behavior in dating, causes and effects of social life. The findings of this study are premarital sexual behaviorisasymptomatic and has been regarded asacommon practice when dating. The roots of this behavior is the existence of ataboothing that matters relating to sex. In addition, given the lack of sex education makes adolescents who have high curiosity was searching for information onminors and the mediaso that the confirmation has not been received correctly. This is what causes deviant behavior. The impact of premarital sexual behavior led to a shift in the value of the sanctity of the institution of marriage. Sex performed after entering the marriage will happen but the reality is sex do when dating. Keywords: sex, teen, dating, social deviation